A Polymorphism in the Melanocortin 4 Receptor Gene (MC4R:c.92C>T) Is Associated with Diabetes Mellitus in Overweight Domestic Shorthaired Cats. (26th December 2013) - Forcada, Y.; Holder, A.; Church, D.B.; Catchpole, B.
<x xml:space="preserve">Abstract</x> Background Feline diabetes mellitus (DM) shares many pathophysiologic features with human type 2 DM. Human genome‐wide association studies have identified genes associated with obesity and DM, including melanocortin 4 receptor (MC4R), which plays an important role in energy balance and appetite regulation. Hypothesis/Objectives To identify single nucleotide polymorphisms (SNPs) in the feline MC4R gene and to determine whether any SNPs are associated with DM or overweight body condition in cats. Animals Two‐hundred forty domestic shorthaired (DSH) cats were recruited for the study. Of these, 120 diabetics were selected (60 overweight, 60 lean), along with 120 nondiabetic controls (60 overweight and 60 lean). Males and females were equally represented. Methods A prospective case‐control study was performed. Genomic DNA was extracted from blood samples and used as template for PCR amplification of the feline MC4R gene. The coding region of the gene was sequenced in 10 cats to identify polymorphisms. Subsequently, genotyping by restriction fragment length polymorphism (RFLP) analysis assessed MC4R:c.92C > T allele and genotype frequencies in each group of cats. Results No significant differences in MC4R:c.92C>T allele or genotype frequencies were identified between nondiabetic overweight and lean cats. In the overweight diabetic group, 55% were homozygous for the MC4R:c.92C allele, compared to 33% of the lean diabetics and 30% of the nondiabetics. The differences between the overweight diabetic and the nondiabetics were significant (P < .01). Conclusions and Clinical Importance We identified a polymorphism in the coding sequence of feline MC4R that is associated with DM in overweight DSH cats, similar to the situation in humans.